Analyzing the factors and challenges affecting the operation of modern apprenticeships from the students’ perspective: a case study in finance and business vocational education / Yan Wang ... [et al.] - Yan Wang; Abdullah, Nabilah; Isa, Badrul; Mingyu Wu (Universiti Teknologi MARA, 2025)
The effective operation of modern apprenticeship programs necessitates addressing the demands of multiple stakeholders, including apprentices influenced by macro entities like governments, businesses, and schools and micro agents such as corporate mentors, teachers, and family members. This study surveyed 123 students from five vocational colleges in Zhejiang Province, achieving 100 valid questionnaires, and conducted structured interviews with 40 finance and business students at Jiaxing Vocational and Technical College. Results highlight the significant positive effects of coordination mechanisms, institutional support, safety assurances, and guidance quality on apprenticeship efficacy. The key challenges discovered include adapting to new technologies, time management, and workplace efficiency, with notable concerns over school policies, working conditions, and compensation. The study proposes enhancing policy support, communication, instructional resources, working conditions, and remuneration to improve program outcomes.